2003
DOI: 10.1016/s1535-6108(03)00132-6
|View full text |Cite
|
Sign up to set email alerts
|

A multigenic program mediating breast cancer metastasis to bone

Abstract: We investigated the molecular basis for osteolytic bone metastasis by selecting human breast cancer cell line subpopulations with elevated metastatic activity and functionally validating genes that are overexpressed in these cells. These genes act cooperatively to cause osteolytic metastasis, and most of them encode secreted and cell surface proteins. Two of these genes, interleukin-11 and CTGF, encode osteolytic and angiogenic factors whose expression is further increased by the prometastatic cytokine TGF bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
2,270
4
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,345 publications
(2,386 citation statements)
references
References 45 publications
93
2,270
4
19
Order By: Relevance
“…Not only MMP-2 has pro-invasive activities, but also MMP-1 overexpression has been shown in a variety of advanced carcinomas, being associated with poor prognosis (Murray et al, 1998a, b;Ito et al, 1999;Fujimoto et al, 2008;Okuyama et al, 2008). High levels of MMP-1 expression have been detected in human breast cancer cells with elevated metastatic capacity towards the bone, providing evidence for its role in cancer cell invasion and metastasis (Kang et al, 2003;Okuyama et al, 2008). However, the molecular mechanism by which P-cadherin expression induces the secretion of these both enzymes to the medium remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Not only MMP-2 has pro-invasive activities, but also MMP-1 overexpression has been shown in a variety of advanced carcinomas, being associated with poor prognosis (Murray et al, 1998a, b;Ito et al, 1999;Fujimoto et al, 2008;Okuyama et al, 2008). High levels of MMP-1 expression have been detected in human breast cancer cells with elevated metastatic capacity towards the bone, providing evidence for its role in cancer cell invasion and metastasis (Kang et al, 2003;Okuyama et al, 2008). However, the molecular mechanism by which P-cadherin expression induces the secretion of these both enzymes to the medium remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that metastasis of tumors to specific organs can be aided by interactions between chemokine receptors on cancer cells and their ligands in the target organs. For example, CXCR4 stimulates metastasis of breast cancer to the bone and lung where its ligand CXCL12 is abundant (Mu¨ller et al, 2001;Kang et al, 2003). We have recently shown that CXCR3 is responsible for LN metastasis of mouse melanoma cells B16F10, without affecting that to the lung (Kawada et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the DNA fragments responsible for these effects did not code directly for OPN protein, or even for any protein, rather they acted as competitors for binding of the transcription factor TCF-4, which suppresses OPN expression. Finally, while studies correlating elevated OPN expression with increased malignancy of a variety of cell lines are too numerous to list here, recently several groups have noted elevated OPN expression associated with the metastatic phenotype following selection and expression profiling of metastatic and nonmetastatic variants of human breast cancer cells (Urquidi et al, 2002;Kang et al, 2003).…”
Section: Opn In Tumorigenesis: Animal Studiesmentioning
confidence: 99%